2013
DOI: 10.1134/s2070205113050122
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of plasma paste boronized AISI 8620 steel in borax paste mixtures

Abstract: In the present study, AISI 8620 steel was plasma paste boronized by using various borax paste mix tures. The plasma paste boronizing process was carried out in a dc plasma system at a temperature of 973, 1023 and 1073 K for 2, 5 and 7 h respectively in a gas mixture of 70% H 2-30% Ar under a constant pressure of 10 mbar. The properties of the boride layer were evaluated by optical microscopy, X ray diffraction, the micro Vickers hardness tester and the growth kinetics of the boride layers. The thickness of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 37 publications
(48 reference statements)
0
9
0
4
Order By: Relevance
“…Industrial boriding processes can be applied to a wide range of steel alloys including carbon steel, low alloy-steel, tool-steel and stainless-steel etc. [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Industrial boriding processes can be applied to a wide range of steel alloys including carbon steel, low alloy-steel, tool-steel and stainless-steel etc. [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Equation (26) coincides with Equation (7); this result implies the equivalence between both diffusion models. Table 2 shows different values of boron activation energies (the minimum boron energy value) in some steels [ 9 , 13 , 38 , 39 , 40 ] taken from the literature. The observed differences in the values of activation energies are related to various factors including the chemical compositions of steels, the nature of the boriding process, the selected boriding parameters, the approach used for the calculation, the physical state of the boron source, and the chemical reactions governing the supply of active boron.…”
Section: Discussionmentioning
confidence: 99%
“…The observed differences in the values of activation energies are related to various factors including the chemical compositions of steels, the nature of the boriding process, the selected boriding parameters, the approach used for the calculation, the physical state of the boron source, and the chemical reactions governing the supply of active boron. For example, Gunes et al [ 9 ] employed the plasma-paste boriding for treating the AISI 8620 steel. The estimated values of activation energies were directly dependent on the chemical composition of the boron-paste mixtures from 99 to 108 kJ·mol −1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated value in this study is comparable with the values reported in the literature as seen in Table 2. [16][17][18][19][20][21] A contour diagram describing the evolution of the boride-layer thickness as a function of the boriding parameters (the time and the temperature) is shown in Figure 7. This contour diagram can be used for two purposes: (1) to predict the coating-layer thickness with respect to the processing parameters, namely, the time and temperature; (2) to determine the value of the processing time and temperature for obtaining a predetermined coatinglayer thickness.…”
Section: Kineticsmentioning
confidence: 99%